Psoriasiform syphilis: a challenge - Antônio Pedro Schettini; José Carlos Sardinha; Elyana Almeida Marques; Cesare Massone (PAGEPress Publications, 2021)
Syphilis is one of the greatest masqueraders in dermatology, like mycosis fungoides or sarcoidosis. In fact, secondary syphilis can simulate different dermatological conditions, not only clinically but also histopathologically. A 34-year old Brazilian man from Manaus (Amazonas) attended our Department complaining for 2 weeks of asthenia, weight loss and multiple asymptomatic disseminated erythematous papules and scaly plaques with well-defined borders and a tendency to confluence were observed on the trunk, neck and extremities, clinically similar to psoriasis guttata. The skin biopsy and laboratory tests disclosed secondary syphilis and the patient was treated with intramuscular benzathine penicillin with prednisolone, with a complete resolution. Psoriasiform syphilis, which imitates psoriasis, was well known by old dermatologists and was called syphilide psoriasiforme or psoriasis syphilitique. Psoriasiform syphilis is one of the atypical presentations of secondary syphilis and dermatologists should be aware of psoriasiform syphilis in order not to improperly treat syphilis patients with immunosuppressive drugs; also, pathologists should be aware of secondary syphilis histopathological features.